Two days of antithymocyte globulin are associated with a reduced incidence of acute and chronic graft‐versus‐host disease in reduced‐intensity conditioning transplantation for hematologic diseases. Issue 5 (23rd October 2012) - Crocchiolo, Roberto; Esterni, Benjamin; Castagna, Luca; Fürst, Sabine; El‐Cheikh, Jean; Devillier, Raynier; Granata, Angela; Oudin, Claire; Calmels, Boris; Chabannon, Christian; Bouabdallah, Réda; Vey, Norbert; et al.
Abstract BACKGROUND: The optimal combination of fludarabine, busulfan, and antithymocyte globulin (ATG) for reduced‐intensity conditioning (RIC) transplantation has not been established. ATG plays a pivotal role in the prevention of graft‐versus‐host disease (GvHD), but it is associated with a higher relapse rate and an elevated incidence of infections when high doses are used. METHODS: The authors retrospectively compared 2 different doses of ATG combined with fludarabine and busulfan in 229 adult patients who underwent transplantation at their institution. ATG was administered over 1 day (FBA1) or over 2 days (FBA2) at a daily dose of 2.5 mg/kg. RESULTS: There were 124 patients in the FBA2 cohort and 105 patients in the FBA2 cohorts. Patients in the FBA2 cohort were older and more frequently underwent transplantation from an unrelated donor; 93% of patients in the FBA2 cohort received intravenous busulfan versus only 5% in the FBA1 cohort. The incidence of grade 2 through 4 acute GvHD was 23% in the FBA2 cohort versus 42% in the FBA1 cohort (P = .002); the incidence of grade 3 through 4 acute GvHD was 10% versus 23%, respectively (P = .006); and the incidence of chronic GvHD was 35% versus 69%, respectively (P < .0001). The 2‐year rates of overall survival, nonrelapse mortality, and relapse/progression for the FBA1 and FBA2 cohorts were 65% versus 67%, respectively (P = .99), 20% versus 19%, respectively (P = .61), and 30% versus 19%, respectively (P = .09). The results were confirmed in multivariate analysis. CONCLUSIONS: The use of ATG at a dose of 5 mg/kg was correlated significantly with reduced incidence and severity of GvHD without impairing disease control. Taken together, the current results suggest that this conditioning represents a step forward in the optimization of RIC. Cancer 2013. © 2012 American Cancer Society.